2002
DOI: 10.1136/heart.88.6.597
|View full text |Cite
|
Sign up to set email alerts
|

The economic burden of coronary heart disease in the UK

Abstract: Objective: To estimate the economic burden of coronary heart disease in the UK using both direct and indirect costs. Design and setting: A prevalence based approach was used to assess coronary heart disease related costs from the societal perspective. Patients: All UK residents in 1999 with coronary heart disease (ICD 9 codes 410-414 and ICD10 codes I20-I25). Main outcome measures: Direct health care costs were estimated from spending on prevention, accident and emergency care, hospital care, rehabilitation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
120
0
8

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(132 citation statements)
references
References 15 publications
0
120
0
8
Order By: Relevance
“…23,24 This is a disappointingly small contribution, particularly when considering the large financial and political resources being consumed. 13,24,25 Thrombolysis likewise accounted for only 25% of the deaths prevented by initial treatments for acute myocardial infarction. This was much less than aspirin and cardiopulmonary resuscitation, as in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 This is a disappointingly small contribution, particularly when considering the large financial and political resources being consumed. 13,24,25 Thrombolysis likewise accounted for only 25% of the deaths prevented by initial treatments for acute myocardial infarction. This was much less than aspirin and cardiopulmonary resuscitation, as in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Using another prevalence approach, Liu et al (39) determined the direct cost of CAD in the UK to be $4.7 billion, an estimate four times higher than the UK cost of CAD given in the previous study (42). Direct costs of CAD were mainly driven by hospitalization costs (53%) and drug treatment (32%).…”
Section: Cadmentioning
confidence: 99%
“…Nine studies (12,(35)(36)(37)(38)(39)(40)(41)(42) reported costs associated with CAD overall or specifically for myocardial infarction (MI), acute coronary syndrome (ACS) and angina. These studies are summarized in Table 5 and are discussed in more detail below.…”
Section: Cadmentioning
confidence: 99%
“…A recent study into the economic burden of CHD in the UK estimated the cost of CHD to the UK healthcare system in 1999 as £1.73 billion, rising to £7.06 billion when informal care and productivity losses were included. 7 There has been a significant increase in prescriptions for the treatment and prevention of CHD since 1999. The combined cost of lipidlowering drugs, including statins, and antihypertensive drugs in 2001 was £861 million, an increase of £171 million on the previous year.…”
Section: Significance In Terms Of Ill-health (Burden Of Disease)mentioning
confidence: 99%